Analysis of the tool nose radius influence in the machining of a green ceramic material - Gonçalves Júnior, Marcos [UNESP]; de Angelo Sanchez, Luiz Eduardo [UNESP]; França, Thiago Valle [UNESP]; Fortulan, Carlos Alberto; da Silva, Rodrigo Henriques Lopes; Foschini, Cesar Renato [UNESP] (Springer Nature, 2019)
Advanced ceramics are applied to several technological applications, and they have special properties. However, the advanced ceramics have poor machinability at the sintered condition, the tool suffers a high tool wear rate, which leads to material removal constraints, and they are usually machined by grinding. Further, the green state machining of advanced ceramics has been investigated as a method for the manufacturing of complex shapes, which provides an alternative for fast manufacturing of near net shape ceramic parts. Some studies have been analyzed the characteristics of green ceramics machining. Although, there are no studies that evaluated the tool nose radius effects at the machining forces and surface roughness during the turning of green ceramic parts. Besides, cylindrical compacted samples were pressed isostatically at 200 MPa, and then the workpieces are turned at constant cutting conditions using three different tool nose radius (0.05, 0.1, and 0.2 mm). The workpieces were analyzed (forces, surface roughness, and SEM images) at the green state first, sintered, and then analyzed again. The results show that the tool nose radius influences the forces, mainly the feed (Ff) and passive (Fp) forces, and there is an increase in the forces between the first and the last pass because of the tool wear. Furthermore, the workpiece offers more resistance to the axial movement than to the others, and as long as the tool wear become larger, the contact area and forces increase. In this sense, the smallest contact area leads to higher pressure and more severe wear conditions, which accelerates the tool wear. Therefore, the abrasion is the predominant wear mechanism, which was characterized by parallel grooves, orthogonal to the cutting edge. Moreover, the 0.05-mm nose radius introduced severe damages on the compact surface, which favors the pulling out of the green compact agglomerates. The increase of tool nose radius can reduce the compact surface roughness (Ra) after machining, although the best condition for tool wear was 0.1 mm. Finally, the surface finishing of the green workpiece has a direct influence on the sample after sintering, and the green state damages are conducted to the final workpiece compact.
Keywords: Green ceramic; Machining forces; Nose radius; Surface finishing